5. OUTCOMES OF PREECLAMPSIA MANAGEMENT AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the clinical, para-clinical characteristics and analyze pregnancy managementresults in preeclamptic patients.Methodology: A retrospective descriptive study was conducted from January 2019 to December2021 on 316 patients diagnosed with preeclampsia, severe preeclampsia and eclampsia at the NationalHospital of Obstetrics and Gynecology.Results: Mild preeclampsia and severe preeclampsia were most common in maternal age from 20-34years old (62.97%), mainly in the group of late preterm birth with gestational age from 33-36 weeks(44.7% and 48.0%, respectively). Hypertension and edema were recorded in the majority of patients.Patients with positive proteinuria were 94.3%, 10.4% of patients with serum urea > 6.6 mmol/l; 7.6%of all had serum creatinine > 106 µmol/l; 51.6% had uric acid > 400 µmol/l; 16.5% had GOT/GPT> 70 IU/l. Pregnant women with platelets
Keywords: Pre-eclampsia, eclampsia, National Hospital of Obstetrics and Gynecology.